Influence of Smallanthus sonchifolius (Yacon) on the Activity of Antidepressant Drugs in Mice - Sylwia Wośko (MDPI AG, 2021)
Depression is one of the most common mental disorders in the world that negatively affects the daily functioning of patients. Numerous studies are currently being conducted to examine the antidepressant potential of innovative synthetic compounds and herbal substances. Yacon, Smallantchus sonchifolius, belongs to plants with numerous health-beneficial properties. Yacon-based products are regarded as a functional food. In our study, we attempted to check whether administration of Yacon tuber extract would have an antidepressant effect in the forced swim test (FST) in mice and whether its intake could influence the activity of conventional antidepressant drugs with different mechanisms of action, i.e., imipramine hydrochloride, fluoxetine hydrochloride, and reboxetine mesylate. The spontaneous locomotor activity of the tested mice was also investigated to eliminate any false-positive results. We demonstrated that an intragastric administration of the Yacon tuber extract at a dose of 100 mg/kg induced the antidepressant-like behavior in the FST in mice and that a combined administration of the sub-effective doses of the Yacon extract (50 mg/kg) with imipramine hydrochloride (7.5 mg/kg), fluoxetine hydrochloride (20 mg/kg), or reboxetine mesylate (5 mg/kg) significantly reduced the immobility time of animals in this behavioral test. The obtained results were not affected by the increased locomotor activity of the tested subjects. In conclusion, our findings suggest that Yacon tuber extract is promising as an alternative mood-improving product since it possesses an antidepressant potential and it can acts synergistically with conventional antidepressant drugs.